Model Sosialisasi Nilai-Nilai Sila Ke-4 Pancasila Menggunakan Modifikasi Strategi Physical Self Assessement Dan Point Counterpoint Pada Karang Taruna Di Desa Bangsri Kecamatan Karangpandan Kabupaten Karanganyar Tahun 2016 - Aslamudasih, Endang; , Dr. Ahmad Muhibin, M.Si (2016)
This study aimed to describe the model of socialization of the values princeple 4th Pancasila using a modification strategy Physical Self Assessment and Point Counterpoint at Karang Taruna Mekar Pelangi, Bangsri, Karangpandan Karanganyar, describes an increain the enthusiasm Karang Taruna Mekar Pelangi Bangsri, Karangpandan, Karanganyar. The Data conducted by informant, place and event of socialization model of the values 4th principle of Pancasila. The techniques to conduct by observation, interviews, and documentation. The techniques analyzing used flow. This socialization models consist of planning, implementation testing, evaluation, improvement and refinement of the model. The resultsof this study indicate that the enthusiasm of Karang Taruna Mekar Pelangi Bangsri, Karangpandan, Karanganyar before the trial is held as many as eigh people (32%). After testing the model is through a model of socialization values 4th principle of Pancasila using a modification strategy Physical Self Assessment and Point Counterpoint, the test I increased to 16 participants (64%) and test models II, rising to 21 people ( 84%) 25 members of karang taruna.